Parental alcohol-specific rules effectively reduce adolescents' tobacco and cannabis use: A longitudinal study. (1st November 2020) - Koning, Ina; de Looze, Margaretha; Harakeh, Zeena
Highlights: Strict alcohol-specific parental rules reduce adolescent tobacco and cannabis use. These are the results of a longitudinal study with a two-year time span. The effects are indirect and run via adolescent alcohol use. Parenting style may moderate the effect of alcohol-specific rules. Abstract: Aims: The current study aimed to longitudinally examine the direct and indirect effects (via alcohol use) of parental alcohol-specific rule-setting on adolescent tobacco and cannabis use. Based on the gateway hypothesis, we expected parental alcohol-specific rules to affect adolescent tobacco and cannabis use through adolescent alcohol use. Design and participants: A longitudinal design including three waves and 906 Dutch adolescents ( M age = 13.51 years, SD = 0.60) was used to apply zero-inflated Poisson models (ZIP). Measurements: Self-report questionnaires measured adolescents' perceived rules about alcohol at T1, cigarette use at T1 and T3 (frequency of life-time and current smoking), cannabis use at T1 /T3 (frequency of yearly and monthly use) and frequency of monthly alcohol use at T1 /T2 . Findings: Stricter alcohol-specific rules at T1 predicted lower incidence and prevalence rates of cigarette (life-time: β = −0.20, p < .00; current: β = −0.21, p = .04) and cannabis use (monthly: β = −0.43, p = .02; yearly: β = −0.28, p = .19) two years later (T3 ). This direct effect was no longer significant when alcohol use at T1 was controlled for. Moreover, a significant indirect effect of alcohol-specific rules at T1 on tobacco and cannabis use T3 via monthly alcohol use T2 was found. Conclusions: The current study demonstrated that strict rules regarding alcohol may not only reduce alcohol but subsequently also other substance use such as tobacco and cannabis. Thus, interventions targeting the prevention of alcohol use, which appears to serve as a gateway, also affects the involvement in other substances.